The Use of Influence Tactics in Politicized Organizations: A Look from Gender Perspective - Bodla, Mahmood A. (Information Management and Business Review, 2013)
The politics is one of the unavoidable constituent of organizational climate in all types of business organizations. Antecedents and consequences of organizational politics and use of influence strategies are very important to consider in an organizational setup when allocating resources and satisfying the interdependencies. However, little is known about the differences among males and females how they use these influence tactics. In this review, the authors have proposed a model which explicitly elaborates the view how the gender differences interact with perceptions of organizational politics when it impacts on job performance. The previous literature supports the fact that males and females differ significantly on perceptions of politics and work performance relationship. The proposed theoretical model for research in multiple dimensions, i.e. power and politics, influence tactics and political behavior may unveil the players’ behaviors in politicized organizations.